The Mediating Role of User Satisfaction in the Relationship between UTAUT Constructs and User Behavior in Digital Public Service Applications - Hildawati Hildawati; Dedy Afrizal; Lis Hafrida; Dina Purnamasari; Ahmad Luthfi (West Science Social and Humanities Studies, 2026)
This study extends the Unified Theory of Acceptance and Use of Technology (UTAUT) to explain why citizens frequently abandon digital public services despite substantial government investment in e‑government platforms. It focuses on Riau Province, Indonesia, and positions User Satisfaction as a central mediator linking four UTAUT antecedents—Performance Expectancy, Effort Expectancy, Social Influence, and Facilitating Conditions—to actual usage behavior. Adopting a deductive quantitative design, the research uses a stratified random survey of 240 e‑government users and analyzes the data with PLS‑SEM, supported by rigorous tests of reliability, validity, common‑method bias, and predictive relevance. The model explains 80.1% of the variance in User Satisfaction and 80.2% in User Behavior, indicating strong explanatory and predictive power. Results show that Performance Expectancy, Social Influence, and Facilitating Conditions significantly increase satisfaction, while Performance Expectancy, Facilitating Conditions, and User Satisfaction itself are key direct predictors of continued use. User Satisfaction also mediates the effects of performance expectancy, social influence, and facilitating conditions on behavior. Although Effort Expectancy is not statistically significant at the 5% level, it exhibits the largest effect size on satisfaction, underscoring the structural importance of ease of use. Theoretically, the study validates an under‑explored affective pathway in mandatory settings; practically, it offers a roadmap for shifting from technology‑centric to citizen‑centric digital governance.